Comparison of physical and acceptability tests of extra oral suction in rsgm ugm prof. Soedomo - Sari, Dian Permata; Wibowo, Danang Sri (Universitas Gadjah Mada, 2024)
The spread of COVID-19 through aerosols and droplets occurs during dental treatment. Dentists use high-volume suction (HVS) and saliva ejectors to suction saliva, blood, and water from the oral cavity. Since the pandemic, prototyping, production, and use of extraoral suction (EOS) have increased. EOS comprises HEPA (High-Efficiency Particulate Air), plasma ions, and ultraviolet (UV) filters. This study was used to see the effectiveness of the use of EOS through a comparison of physical and acceptability tests on the use of EOS at UGM Prof. Sodeomo Dental Hospital using three EOS brands, Coxo™, Eighteeth™ Vacstation, and Eostra™. Physical Test is used to assess the ability of a tool when used—Acceptability Test to assess user acceptance of EOS based on usage experience. The study was conducted at the UGM Prof. Soedomo Hospital (Professional Education Clinic, Resident Education Clinic, General Service Unit, and Specialistic Service Unit) in 2021 with 90 respondents who were EOS users. The EOS with the most incredible suction power, noise figure, and electrical power was Eostra™, while based on user experience, the EOS that was more accepted and more comfortable for users to use was Coxo™. EOS reduces aerosol exposure during dental treatment, and based on this study, EOS that had good capacity was not necessarily comfortable to use by users; this was because each brand had advantages and disadvantages, so the selection of EOS was adjusted to the capacity of the operator and the practice site.